2021
DOI: 10.1007/s10856-021-06529-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a PVA drug delivery system for controlled release of a Tramadol–Dexketoprofen combination

Abstract: The local administration of analgesic combinations by means of degradable polymeric drug delivery systems is an alternative for the management of postoperative pain. We formulated a Tramadol–Dexketoprofen combination (TDC) loaded in poly(vinyl alcohol) (PVA) film. Films were prepared by the solvent casting method using three different molecular weights of PVA and crosslinking those films with citric acid, with the objective of controlling the drug release rate, which was evaluated by UV–vis spectrometry. Non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…2b) shows a crystalline endotherm at 156.45 °C that seems to correspond with citric acid melting point (154.11 °C). On the other hand, F2 shows a shift in PVA endotherm at 194.30 °C to 177.06 °C, which can be due to the polymerization process and crosslinking with citric acid [22]. However, in this formulation, it is not possible to see PVA second endotherm at 323.61 °C or any other related to chitosan and citric acid.…”
Section: Compatibility Testsmentioning
confidence: 78%
See 2 more Smart Citations
“…2b) shows a crystalline endotherm at 156.45 °C that seems to correspond with citric acid melting point (154.11 °C). On the other hand, F2 shows a shift in PVA endotherm at 194.30 °C to 177.06 °C, which can be due to the polymerization process and crosslinking with citric acid [22]. However, in this formulation, it is not possible to see PVA second endotherm at 323.61 °C or any other related to chitosan and citric acid.…”
Section: Compatibility Testsmentioning
confidence: 78%
“…5.a) showed a reduction in the drug released at 24 hours (88.40 ± 3.94 %) but also reduced burst release compared to F1 (1h: 26,81 ± 3.25 %, 6h: 58.16 ± 3.07 %). This profile can be attributed to the presence of intra-and inter-crosslinked PVA tubules by the citric acid, which reduce porosity, difficult the penetration of water molecules and reduce wettability [22]. Nonetheless, F3 (Fig.…”
Section: In Vitro Release Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…A study conducted by Palla N et al also reported the absence of interaction between tramadol HCl and HPMC (Palla et al, 2013). Another study suggests that there is no visible interaction between tramadol HCl and commonly used pharmaceutical excipients (Flores-Arriaga et al, 2021).…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) and Scanning ...mentioning
confidence: 94%
“…In addition, the adhesion strength of the hydrogel to the US is also weakened by its swelling features [ [20] , [21] , [22] ]. Other preparation techniques for drug carriers include 3-D printing [ [23] , [24] , [25] , [26] ], solvent casting [ 27 ], and micro-nano capsules [ [28] , [29] , [30] , [31] ]. However, the drug-loading process (type, dose) is usually carried out before polymer molding and cannot be adjusted in use.…”
Section: Introductionmentioning
confidence: 99%